Urgent pre-contractual judiciary in the field of public deals - Dahma, Marwan (Social Empowerment Journal, 2020)
The lawsuit field before the judge of urgency in the field of concluding administrative contracts and public deals enables the contracting dealer to intervene in order to ensure the legality of procedures related to transparency and openness, by being a control tool for the administrative judge over the course of concluding public deals,This type of lawsuit was introduced according to Articles 946 and 947of law No.08/09 relating to civil and administrative procedures, Although this step came late compared to its french counterpart, it is a welcome trend that confirms the legislator’s keenness to keep abreast of developments in the field of public deals, which are the best way to implement development programs, and a tool for the field embodiment of public Investments and projects to build a competitive economy.